Calidad de áreas verdes urbanas con el bienestar en la salud de la población del Distrito Iquitos, Loreto. 2024 - Vega Guerra, Neyvis Marielena (2024)
It is a non-experiemocional quantitative research of the exploratory type - descriptive, analytical, transversal. The information was obtained through a structured interview of the population that lives in places near green areas of the Iquitos district on Calle 30 de Agosto, Sargento Lores I, Urb. Virgen de Loreto and Sargento Lores II, with a total of eighty (80 ) interviews, with a level of instrument reliability, Cronbach's Alpha of 0.774. The normality of the data was determined with the Shapiro Wilk test, which reports in most groups and sections that the data have a normal distribution, so the Pearson Correlation test was used. However, the exception is the group of Urb. Sergeant Lores I in relation to the Perception of the Quality of Urban Green Areas, where the data of this group does not have a normal distribution, so the Rho Spearman test was used. Which allowed us to conclude: That the infrastructure of green areas must be improved, such as play areas, trails and basic services, improve security with better lighting, regular patrols and surveillance systems and green areas be safe spaces; Community participation in the maintenance and management of green areas should be encouraged, through cleaning days, gardening workshops and the creation of neighborhood committees to care for parks. For their part, local authorities must promote the creation and maintenance of quality green areas, based on the needs and expectations of the community and continuous monitoring of their condition to facilitate decision-making and future improvements. The statistical analysis shows that in Calle 30 de Agosto and Urb. Sargento Lores I there are significant correlations between the perception of the quality of green areas and the impact on health and well-being, although of an opposite nature (negative and positive, respectively). While in Urb. Sargento Lores II and Urb. Virgen de Loreto, no significant correlations were found, which suggests that other factors may be influencing the health and well-being of the population.